Fecal Excretion of Salmonella enterica Serovar Typhimurium Following a Food-Borne Outbreak - Murase, Toshiyuki (American Society for Microbiology, 2000)
Fecal excretion of Salmonella enterica serovar Typhimurium organisms was observed in patients and in people not showing symptoms who were involved in an outbreak of food-borne infection with this organism. Excretion of organisms was prolonged in the patients who were given antimicrobial drugs compared with those who were not. The isolates were indistinguishable by their pulsed-field gel electrophoresis patterns and biotyping from the strain recovered from the roast pork that had been consumed by all of the people. This indicates that these isolates obtained from the infected people had originated in the contaminated pork.